The Effect of Teamwork and Job Satisfaction on Performance Mediated by Role Conflicts at Bank Indonesia Representative Office in North Sumatra Province - Ibrahim Hasim Hasibuan; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
Human resources are one of the most strategic and fundamental factors in an organization. Compared to other factors, human resources are the most valuable asset. The role of human resources will greatly determine the success or failure of the organization in achieving the vision and mission that has been set, therefore human resources are very important for the organization. In addition to determining success, the position of human resources in the organization today is not only as a means of production but also as a driver and determinant of organizational activities. The results of this study are as follows: Job satisfaction has a positive and significant effect on performance with the original sample value of 0.246 and p values of 0.000. Job Satisfaction had a positive and significant effect on Role Conflict with an original sample value of 0.545 and p values of 0.000 Teamwork had a positive and significant effect on Performance with an original sample value of 0.268 and p values of 0.004. Teamwork had a positive and significant effect on Role Conflict with the original sample value of 0.560 and p values of 0.002. Role Conflict had a positive and significant effect on Performance with the original sample value of 0.446 and p values of 0.000. Role Conflict had a positive and significant effect on Performance with the original sample value of 0.446 and p values of 0.000. Job Satisfaction had a positive and significant effect on Performance through Role Conflict indirectly with the original sample value of 0.243 and p values of 0.002. Teamwork had a positive and significant effect on Performance through Role Conflict indirectly with the original sample value of 0.161 and p values of 0.007.